Challenges for dark matter direct search with SiPMs - Razeto, Alessandro; Rossi, Nicola (Frontiers in Physics, 2024)
Liquid xenon and liquid argon de-1 tectors are leading the direct dark matter search 2 and are expected to be the candidate technol-3 ogy for the forthcoming generation of ultra-4 sensitive large-mass detectors. At present, the 5 scintillation light detection in those experiments 6 is based on ultra-pure low-noise photo-multipliers. 7 To overcome the issues in terms of the extreme 8 radio-purity, costs, and technological feasibil-9 ity of the future dark matter experiments, the 10 novel SiPM-based photo-detector modules look 11 promising candidates, capable of replacing the 12 present light detection technology. However, 13 the intrinsic features of SiPMs may limit the 14 present expectations. In particular, interfering 15 phenomena, especially related to the optical 16 correlated noise, can degrade the energy and 17 pulse shape resolutions. As a consequence, the 18 projected sensitivity of the future detectors has 19 to be reconsidered accordingly. 20 Keywords Noble gas detector • TPC • light 21 yield • dark matter • SiPM • liquid argon • 22 liquid xenon 23